Different but valuable: Anthropogenic habitats as genetic diversity reservoirs for endangered dry grassland species – A case study of Stipa pennata. (April 2020) - Klichowska, Ewelina; Szczecińska, Monika; Ślipiko, Monika; Nobis, Marcin
Highlights: Populations from anthropogenic habitats do not suffer from genetic depauperation. For steppe species anthropogenic habitats are rather refuges than substitution habitats. Secondary habitats are reservoirs for threatened xerothermic species. Competition and habitat connectivity indicate habitats usefulness for xerothermic species. Abstract: Increasing urbanisation has led to the fragmentation of natural habitats and biodiversity decline. In Central Europe, this fate has befallen semi-natural xerothermic grasslands. However, in the case of species well adapted to open habitats, urbanisation may positively affect dispersal. In many places specialised xerothermic species start to spread in secondary habitats such as roadsides or railway embankments. However, little is known about the genetic variability of such newly-established populations. In an era of growing anthropogenic pressure, understanding the role of secondary, anthropogenic habitats in the maintenance biodiversity should be considered a crucial issue in the conservation of species associated with Central European dry grasslands. Therefore, on the basis of a combined analysis of xerothermic species abundance, bioclimatic and soil data, and genetic diversity, we wish to examine the suitability of secondary habitats (as substitutes for primary) and to demonstrate their role in the conservation of xerothermic species. Our results suggest that smaller competition for light and greater habitat connectivity indicate suitability of habitats for xerothermic species conservation. On one hand, the occurrence of these species in secondary habitats may be limited by the pressure of expansive grasses, on the other, the negative impact of the latter is buffered by the reduced presence of shrubs, and thus the greater availability of light. Plant communities from secondary habitats are less richness in xerothermic species, and particular species are less abundant, for this reason secondary habitats should be treated more as refuges (with suboptimal conditions) than as substitution habitats. But yet, Stipa pennata populations from secondary habitats do not suffer from genetic depauperation. Populations from secondary habitats are characterised by comparable share of two genotypes, indicating existence of gene flow between populations from south and north-west part of studied area. Through the maintenance of meta-population processes by means of dynamic connectivity between habitats on a landscape scale, secondary habitats possess an undoubtedly high conservation value for xerothermic species.